2016
DOI: 10.1109/tnb.2015.2508718
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Impair Foot-and-Mouth Disease Virus Replication

Abstract: In this study, we evaluated the antiviral activity of gold nanoparticles (AuNPs) against the foot-and-mouth disease virus (FMDV), that causes a contagious disease in cloven-hoofed animals. The anti-FMDV activity of AuNPs was assessed using plaque reduction assay. MTT assay was used for quantitatively measuring the cytopathic effect caused by the viral infection. The 50% cytotoxicity concentration of nanoparticles was measured and found to be 10.4 μg/ml. The virus yield reduction assay showed that AuNP have an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Concomitantly, AuNPs ameliorated the inflammatory response by decreasing the mRNA expression of interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, IFN-γ and inducible nitric oxide synthase [ 97 ]. AuNPs also inhibited attachment and penetration of foot-and-mouth disease virus (FMDV) at the early stages of infection and impaired viral replication at later stages at non-toxic concentrations and at early stage [ 47 ]. AuNPs conjugated with peptide triazoles (AuNP-PT) exhibited significant antiviral effects against HIV-1 compared to the corresponding peptide triazoles alone.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitantly, AuNPs ameliorated the inflammatory response by decreasing the mRNA expression of interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, IFN-γ and inducible nitric oxide synthase [ 97 ]. AuNPs also inhibited attachment and penetration of foot-and-mouth disease virus (FMDV) at the early stages of infection and impaired viral replication at later stages at non-toxic concentrations and at early stage [ 47 ]. AuNPs conjugated with peptide triazoles (AuNP-PT) exhibited significant antiviral effects against HIV-1 compared to the corresponding peptide triazoles alone.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…In addition, the major requirements including cellular entry through the blood-brain barrier and blood-air barrier, tenability and targeted control discharge are feasible with nanomaterials, thus qualifying these materials as potential novel candidates for use in biomedical therapy [ 28 , 29 , 30 ] Nanoparticles have been widely used in antiviral therapy over the last few decades, owing to the development of surface functionalization strategies [ 45 ]. For example, Ag [ 46 ], Au [ 47 ], TiO 2 [ 48 ], SiO 2 [ 49 ], CeO 2 [ 50 ] and CuCl 2 [ 51 ] nanoparticles have been employed against different viruses including hepatitis B virus (HBV) [ 46 ], H3N2 and H1N1 [ 52 ], HIV-1 [ 53 ], herpes simplex virus (HSV) [ 54 ], vesicular stomatitis [ 55 ], foot-and-mouth disease [ 47 ] and dengue virus type-2 [ 51 ]. Recently, Sportelli et al (2020) stated that researchers need to focus on the development of nanomaterial-based technological solutions to fight COVID-19 [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials can inhibit viral replication by interacting with the viral protein/genome or inducing a suppressive environment for intracellular viral replication. AuNPs arrest foot-and-mouth disease virus (FMDV) replication at the post-entry stage and block viral transcription in the host cell by binding to FMDV RNA, sub-genomic RNA, or viral replicative proteins via electrostatic interactions [ 54 , 55 ]. Moreover, several fullerene derivatives can affect the maturation of both wild-type HIV-1 and drug-resistant HIV-1 by inhibiting Gag polyprotein processing, which generates the matrix, capsid, nucleocapsid, and p6 gag proteins required for a functional virus, thereby hindering viral replication [ 56 ].…”
Section: Antiviral Effects Of Nanomaterialsmentioning
confidence: 99%
“…Interestingly, only six of the published articles addressed NM exposure and increased viral susceptibility, whereas results of the remaining nine papers showcased the ability of NMs to inhibit virus titers either through blocking viral entry or through replication. For example, cells exposed to silver nanoparticles were shown to inhibit dengue virus serotype 2 (DENV-2) viral replication and production of progeny viruses (Murugan et al 2015), and inhibit replication of HSV-2 (Hu et al 2014), HIV-1 (Trefry and Wooley 2012), and HSV-2 (Sopova et al 2010), whereas foot-and-mouth disease virus (FMDV) titers were reduced by gold NP (Rafiei et al 2016). Another interesting aspect of these studies showed that the effects of carbon NMs on viral infection varied by the type of nanoparticles tested.…”
Section: Nanoparticle Exposure and Viral Infectionmentioning
confidence: 99%